Cerium oxide nanoparticles: green synthesis and biological applications - Charbgoo, Fahimeh; Ahmad @ Ayob, Mansor; Darroudi, Majid (Dove Medical Press, 2017)
CeO2 nanoparticles (NPs) have shown promising approaches as therapeutic agents in biology and medical sciences. The physicochemical properties of CeO2-NPs, such as size, agglomeration status in liquid, and surface charge, play important roles in the ultimate interactions of the NP with target cells. Recently, CeO2-NPs have been synthesized through several bio-directed methods applying natural and organic matrices as stabilizing agents in order to prepare biocompatible CeO2-NPs, thereby solving the challenges regarding safety, and providing the appropriate situation for their effective use in biomedicine. This review discusses the different green strategies for CeO2-NPs synthesis, their advantages and challenges that are to be overcome. In addition, this review focuses on recent progress in the potential application of CeO2-NPs in biological and medical fields. Exploiting biocompatible CeO2-NPs may improve outcomes profoundly with the promise of effective neurodegenerative therapy and multiple applications in nanobiotechnology.